Towards more efficient burn care: Identifying factors associated with good quality of life post-burn. Issue 7 (November 2015) - Finlay, V.; Phillips, M.; Allison, G.T.; Wood, F.M.; Ching, D.; Wicaksono, D.; Plowman, S.; Hendrie, D.; Edgar, D.W.
Highlights The probability of achieving a high BSHS-B score six months from injury was estimated. Gender, surgery, upper limb burn and BSHS-B score within six weeks were significant predictors. ROC analysis found 90% accuracy overall and 14% specificity at 80% probability of good outcome. ROC analysis in an independent sample confirmed high accuracy of the predictive model. Missing data analysis found that younger patients with smaller TBSA were lost to follow-up.